2017
DOI: 10.12991/marupj.319304
|View full text |Cite
|
Sign up to set email alerts
|

Tartrazine induced changes in physiological and biochemical parameters in Swiss albino mice, Mus musculus

Abstract: Now-a-days synthetic food dyes are being used most commonly as food colorant in confectionaries, drugs and cosmetics. Present study was designed to evaluate the toxic effect of tartrazine, a widely used azo dye, on Swiss Albino mice.Experimental animals were treated with tested dye at a dose level 200mg/kg & 400mg/kg body weight along with normal diet. Various physiological and biochemical parameters were assessed to study the toxic effect of tartrazine. Our study revealed a highly noticeable decrease in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
5
8
0
Order By: Relevance
“…Moreover, both hepatic immunohistochemical research of COX-2 expression and histological structures had been notably altered, supplementation with Vitamin E partly protected against the recorded hepatic biochemical and histological changes caused by exposure to 300 mg/kg of TZ. The findings of this study were consistent with the results of different researches that postulated physiological and biochemical 22 , immunological 23 and histological 24 , severe changes in the liver after administration of tartrazine. Moreover, as reported by Demirkol, et al 25 reported the a dministration of tartrazine at the dose of 7.5mg/kg daily for 30 days lead to an extreme histopathological and cellular change of rat liver.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, both hepatic immunohistochemical research of COX-2 expression and histological structures had been notably altered, supplementation with Vitamin E partly protected against the recorded hepatic biochemical and histological changes caused by exposure to 300 mg/kg of TZ. The findings of this study were consistent with the results of different researches that postulated physiological and biochemical 22 , immunological 23 and histological 24 , severe changes in the liver after administration of tartrazine. Moreover, as reported by Demirkol, et al 25 reported the a dministration of tartrazine at the dose of 7.5mg/kg daily for 30 days lead to an extreme histopathological and cellular change of rat liver.…”
Section: Discussionsupporting
confidence: 92%
“…According to Arefin et al significantly increased levels of CRE and TG are reported in Swiss mice, after applying tartrazine dose 400 mg/kg b.w. by oral gavage [52].…”
Section: Resultsmentioning
confidence: 99%
“…He reported a significant decrease in body weight of treated rats comparing with control. Arefin et al (2017) showed that no mortality and clinical signs among mice treated with Tz but there was growth retardation in mice treated with large dose (400 mg/kg b.wt) but lower dose (200 mg/kg b.wt) didn't affect the body weight gained. On the other hand, Gautum et al (2010) showed that Tz caused significant increase in body weight of rats treated with two doses of Tz (0.2&0.4gm) for 30 days.…”
Section: Discussionmentioning
confidence: 97%